Financial Deepening and Economic Growth in Indonesia - Wasiaturrahma -; Shochrul Rohmatul Ajija; Ramses Muhammad Rizal (MediaTrend, 2019)
The purpose of this study is to analyze the impact of financial deepening on economic growth in Indonesia. The time period studied for this research is from 1975 until2016. This study uses a quantitative research approach in the form of statistics and econometrics regression data. The data used is based on the annual time series data from 1975 until 2016. In this research, two models of testing are used, namely ARDL (Autoregressive Distributed Lag) and ECM (Error Correction Model). The results of this study indicate that financial deepening has a significant negative impact on economic growth in Indonesia. The Broad Money, Government Expenditure and Trade Openness variables influenced the variables of economic growth simultaneously in the period 1975-2016, but only the GDP and Trade openness variables had a significant influence on the dependent variable of GDP during the researched period. Therefore, Bank Indonesia (BI) needs to conduct further research on Broad Money trading (M2) so that the function of economic depth can encourage the growth of GDP Indonesia. In addition, there is a need for policies that will stimulate and facilitate foreign and domestic companies to sell their shares on BEI (Indonesian stock exchange) so that they can be traded by people whose impact will increase Indonesia's economic growth.